Portrait of King Carol II (Confluenţe Bibliologice, 2025)
On May 15, 2014, at the Hanul lui Manuc, was oﬃcially launched the book „Portrait of a King Carol II” by Narcis Dorin Ion, Bucuresti, Oscar Print Ed, 2013.
Keywords: historical personality